The Characters and Meaning of Third Place in Historical Urban Space of Iran - Ebrahimi, Ahad Nejad; Gherehbeiglu, Minoo; Farshchian, Amir Hossein (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2017)
Third place is the interface between work and life and due to the direct connection with urban development. It is a valuable space for attending the community in which one attends voluntarily, informally, and regularly or irregularly. There are such places in urban areas of Iran where people are able to attend in order to do social and religious activities and it seems like that the architectural nature of such spaces has some similarities and differences with the definition of third place. The research question is, â€œwhat are the features of third place in pre-modern cities of Iran and are the features in accordance with the definition of third place?â€. This is a developmental research conducted via the interpretive-historical method. The findings indicate that third place is commonplace in Iranian Cities and some architecture types like public, religious and residential spaces have fundamental similarities with the definitions of third place In Iranian Historical cities, but there are also some differences due to culture, religion, and climate in each region. Third places have widely exited in most applications and religious relations, rituals, and beliefs which demonstrate that brotherhood and communion have significantly influenced the formation of this place. The main issue in this regard is the firm presence of religion and strong ethnocultural ties which have affected the constituents of third place as components like the constant presence of water, creation of special, simple, and defined spaces, respect to adults and providing special furniture for them, and focusing on geometry and aesthetic proportions.